Patronage, Logrolls, and "Polarization": Congressional Parties of the Gilded Age, 1876–1896. Issue 2 (6th June 2016) - Lee, Frances E.
Abstract : According to the quantitative indicators scholars use to measure political polarization, the Gilded Age stands out for some of the most party-polarized Congresses of all time. By contrast, historians of the era depict the two major parties as presenting few programmatic alternatives to one another. I argue that a large share of the party-line votes in the Congress of this period are poorly suited to the standard conceptualization as "polarization, " meaning wide divergence on an ideological continuum structuring alternative views on national policy. Specifically, the era's continuous battles over the distribution of particularized benefits, patronage, and control of political office make little sense conceived as stemming from individual members' preferences on an underlying ideological dimension. They are better understood as fights between two long coalitions competing for power and distributive gains. In short, the Gilded Age illustrates that political parties are fully capable of waging ferocious warfare over spoils and office, even despite a relative lack of sharp party differences over national policy.